Frequency, Causes and Medico-Legal Aspects of Grievous Injury to the Eye after Physical Assault - Shahid, Erum; Fasih, Uzma (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Aims: A medicolegal report is prepared by the medicolegal officer in conjunction with an ophthalmologist in cases of physical assault claiming vision loss. The objective was to report the frequency and cause of grievous injury to the eye after a physical assault. Methods: This was a descriptive cross-sectional study, conducted in the Department of Ophthalmology of a tertiary care hospital in Pakistan from October 2019 to August 2022. A total of 378 medicolegal cases were reported in the ophthalmology outpatient. Among them, 285 patients of physical assault were included with consecutive sampling technique. Results: The mean age of the patients was 33.93±12.96 years. The mean reporting time to an ophthalmologist was 4.1±8.2 days. Simple and grievous injuries were found in 278 (97.5%) and 7 (2.4%) cases, respectively. Among the grievous injuries, 4 (57.2%) were close globe injuries and 3 (42.8%) were open globe injuries. Thirteen (4.5%) were malingers. Domestic violence was observed in 82 (28.8%) study subjects. Conclusion: The frequency of grievous injury to the eye is very low (2.4%) in patients with physical assault. The patients of assault-related grievous injury were mostly males, young age, low level of education, and doing manual jobs. Vitrolage with corneal melting, and firearm injury caused the grievous injury in open globe patterns. Vitreous hemorrhage, retinal detachment, macular hole, and secondary glaucoma were seen among close globe patterns. J Bangladesh Coll Phys Surg 2024; 42: 336-341